2022
DOI: 10.3389/fbioe.2022.929699
|View full text |Cite
|
Sign up to set email alerts
|

Early Pixel Value Ratios to Assess Bone Healing During Distraction Osteogenesis

Abstract: Background: Distraction osteogenesis (DO) is an approach for bone lengthening and reconstruction. The pixel value ratio (PVR), an indicator calculated from X-ray images, is reported to assess the final timing for the external fixator removal. However, the early PVR and its potential influencing factors and the relationship between the early PVR and clinical outcomes are rarely discussed. Therefore, this study was employed to address these issues.Methods: A total of 125 patients with bone lengthening were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Balakumar et al [13] found that PVR may be a reliable indicator of bone graft fusion to aid clinical decision by measuring and analyzing PVR of bone grafts in 30 patients. Some studies have shown gender differences in adults, and Liu et al [1] studied the gender of long bone lengthening and found no signi cant difference which is consistent with our study, and there was no difference in PVR between the genders of children. For the effect of obesity or weight on BMD, Garvey [14] et al concluded that there is an effect in adults, with a signi cant negative correlation between obesity and BMD (β = -0.003).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Balakumar et al [13] found that PVR may be a reliable indicator of bone graft fusion to aid clinical decision by measuring and analyzing PVR of bone grafts in 30 patients. Some studies have shown gender differences in adults, and Liu et al [1] studied the gender of long bone lengthening and found no signi cant difference which is consistent with our study, and there was no difference in PVR between the genders of children. For the effect of obesity or weight on BMD, Garvey [14] et al concluded that there is an effect in adults, with a signi cant negative correlation between obesity and BMD (β = -0.003).…”
Section: Discussionsupporting
confidence: 92%
“…Distraction osteogenesis (DO) is a technique for regeneration of bone, it stimulates bone tissue regeneration and reconstruction by giving the bone tissue a tension of stretching. The pixel-to-value ratio (PVR) is a metric measured by x-ray images that has been used in many studies to assess the time of nal external xator removal [1] [2]. However, all of this studies only describes its in uence after long bone lengthening [3].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has shown that the early PVR was moderately negatively associated with HI and LI, which suggests that the early PVR can effectively reflect the clinical outcome of DO (16). However, the four cortices were taken as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the early PVR seemed to be moderately inversely associated with HI and LI, respectively. In another word, the early PVR of callus may partly reflect the potential clinical outcome for DO [ 25 ]. On the basis of these above, our study further figured out the PVR growth pattern in bone nonunion during DO.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the ratio of the regenerated callus PV to the adjacent bone PV was calculated. The higher PVR indicated that the regenerated callus was closer to the reference bone, whereas the lower PVR reflected a lower immaturity of the callus [ 17 , 25 ]. The formula for the calculations of PVR were as follows:
Fig.
…”
Section: Methodsmentioning
confidence: 99%